Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, Dan Leverage Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2021) - Siti Mufidah Ulya; Sunarto Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
In order to review and discuss the the results of return on asset, debt to equity ratio, company size, and debt to assets ratio on tobin's q, 84 property and real estate limited liability companies listed on the IDX for the years 2015 to 2021 were the research's targets. The study approach utilized was secondary quantitative by means of sampling using purposive sampling received by the final sample of the review a total of 209. Leverage had an impact on company value, according to the analysis's findings, whereas profitability, capital structure, and firm size did not Keywords: company value, profitability, capital-structure, firm size, leverage